A New Synthetic Pathway to Symmetric Bisubstituted Naphthoquinones - Migulin, Vasily A. (Synthesis, 2020)
straightforward and practical synthesis of 2,3-diiodo-1,4-naphthoquinone is reported. Based on the prepared diiodide, a new synthetic approach to symmetric bisubstituted 1,4-naphthoquinones via double Suzuki–Miyaura reaction at room temperature has been researched and developed. The presented general method combines broad-spectrum applicability, efficiency, and simplicity providing target materials in good to quantitative yields.
Keywords: 1,4-naphthoquinone; Finkelstein reaction; Suzuki–Miyaura reaction; Pd catalysis; pinacolboronic esters